Acrylate Hydrogel Modification Using a Cross-Linking Agent for Increasing Multilayer Glazing Flame Resistance; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Litovchenko D.; Burmistrov I.; Panova L.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Kosova N. (Structure Materials, Mechanics and Dynamics of Materials, 2015)
Title screen